Heard on the Birdline, December 15, 1997-March 15, 1998 - Fuller, James L.et al; Iowa Ornithologists' Unionet al (1997)
Summary of the Iowa Birdline update for December 15, 1997-March 15, 1998. Highlights of the update include sightings of two Ross's Gulls, an adult Black-legged Kittiwake, and seven different Snowy Owl observations in December. Very unusual reports of a Common Raven and a Sprague's Pipit were reported in February. Other interesting observations were of a mid-winter sighting of a Summer Tanager in January and February as well as a continued winter presence of White-winged Crossbills. Epson - sheet feed